On Generalizing Stock Market Research to a Broader Class of Markets . - Davis, Darrel W.; Boatsman, James R.; Baskin, Elba F. (The Accounting Review, 1978)
ABSTRACT: The impact of accounting earnings data on bond price behavior is examined for 85 bond issues over the period 1968-1972. Essentially, the study's results indicate that for convertible bonds, certain inferences drawn from stock market research may be extrapolated to this segment of the bond market. That is, accounting data appear to have information content for this market. The study's results concerning nonconvertible bonds indicate that accounting earnings data is incorporated in prices of nonconvertibles, but in a more diffused fashion.